Piwulang Jawa Anak-anak Sedulur Sikep di Kecamatan Sukolilo Kabupaten Pati (Piwulang : Jurnal Pendidikan Bahasa Jawa, 2022)
Sedulur Sikep Sukolilo Pati still holds the theory of laku sikep as a guide to their daily life. One of the theories is not sending their children to formal schools. They believed that formal schools will change the behavior that they have been holding. It also makes formal education unable to be felt by Sedulur Sikep Sukolilo Pati until now. Research data in the form of materials, media, learning resources, methods, and evaluation of learning. Source of research data, namely piwulang Jawa learning instructor. Data collection methods use participatory observation and unstructured interviews. Data analysis uses data reduction techniques, data presentation, and data verification. The results of the study are Javanese piwulang learning components for the children of Sedulur Sikep Sukolilo Pati consist of materials, media, learning resources, methods, and learning evaluation. Piwulang Jawa learning material, including knowledge material, attitude material, and skill material. Piwulang Jawa learning media, namely visual media (inanimate objects and living things). Learning resources in piwulang Jawa, include learning resources from humans, learning resources from materials, and learning resources from the environment. Piwulang Jawa learning methods include lecture method, question and answer method, assignment method, practice method, and exploring method. There are two evaluations of piwulang Jawa learning, namely process evaluation, and outcome evaluation.